Complex sex chromosome system in Eigenmannia sp. (Pisces, Gymnotiformes) - Toledo, L. F. de Almeida; Foresti, H. [UNESP]; Toledo Filho, S. de Almeida (Kluwer Academic Publ, 1984)
Chromosomes of Eigenmannia sp. (7 males and 15 females) collected from the Tietê River in Botucatu (SP, Brazil) were examined from gill, kidney and testicular cells. The diploid chromosome number in males was 2n=31 and in females, 2n=32. In both sexes the number of chromosomal arms was 40. The difference in diploid number was due to the fusion of two acrocentrics. Mitotic and meiotic studies suggested that one of the fused acrocentrics was the Y chromosome. The sex-determining mechanism in Eigenmannia sp. could therefore be XX, AA in the female and X, \-YA A in the males. One of the males presented 2n=30 chromosomes due to the occurrence of another fusion of acrocentrics. C-banding analysis of the mitotic chromosomes revealed constitutive heterochromatin in the centromeric regions of all acrocentrics. However, small metacentrics were C-band negative. The YA chromosome is C-band negative except for a small amount of heterochromatin in the centromeric region. The nucleolar organizer region as identified by Ag-staining is present in the interstitial region of chromosome pair No. 10. © 1984 Dr W. Junk Publishers.